Brachycorythis obcordata (Lindl.) Summerh. (Orchidaceae): A new angiospermic record for Bangladesh - Hoque, MM; Huda, MK (Bangladesh Journal of Botany, 2008)
Brachycorythis (Lindl.) Summerh. of the family Orchidaceae is reported here as a new angiospermic record for Bangladesh flora. Key words: Brachycorythis obcordata, Orchidaceae, New record, Bangladesh doi:10.3329/bjb.v37i2.1732 Bangladesh J. Bot. 37(2): 199-201, 2008 (December)